The Psychological Impact of Divorce on Children and Parental Obligations in Islamic Family Law - Santoso, Budi; Sari, Maya (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2021)
This research examines the psychological impact of divorce on children and the responsibilities of parents in providing emotional and psychological support according to Islamic family law. Using a qualitative approach, this research involves document analysis and in-depth interviews with Islamic legal experts, psychologists, and families who have experienced divorce. The research results show that the emotional stability of children after divorce is very dependent on the comprehensive implementation of hadhanah by parents. Children who receive adequate emotional support from both parents tend to have better mental health. However, the practical implementation of hadhanah principles often faces obstacles due to a lack of understanding and support from the legal and social systems. This research recommends increasing education and support for parents as well as developing post-divorce family counseling programs to ensure children's emotional well-being. Thus, this research contributes to the academic literature and provides practical recommendations for better family law policies in handling divorce cases.